The design of single section microstrip branch line coupler / Maria Awi - Awi, Maria (2006)
The objective of this project is to design a single section microstrip branch line coupler at operation frequency of 2.45 GHz with the coupling factor of 3.5 dB. The aim of the design is to provide a perfect match between all the connected lines of the coupler. The critical parameters that need to be investigated in this project are return loss, insertion loss, coupling and isolation. The coupler was design so that the power signals can be divided equally between the output and coupling port at the operation frequency for the used of several applications in microwave system. The circuit design is simulated using Eagleware Genesys and Eesof Libra Microwave CAD package and finally is fabricated on a microstrip laminate 'RT/Duroid 5870'' with the thickness of 0.5 mm and relative permittivity of 2.33. The fabricated coupler is measured by using a vector network analyzer. Finally, both simulation and measurement results are compared.